Variable angle gray level co‐occurrence matrix analysis of T 2 relaxation time maps reveals degenerative changes of cartilage in knee osteoarthritis: Oulu knee osteoarthritis study - Peuna, Arttu; Hekkala, Joonas; Haapea, Marianne; Podlipská, Jana; Guermazi, Ali; Saarakkala, Simo; Nieminen, Miika T.; Lammentausta, Eveliina (Journal of magnetic resonance imaging, 2018)
Texture analysis methods based on gray level co-occurrence matrices (GLCM) can be optimized to probe the spatial correspondence information from knee MRI T maps and the changes caused by osteoarthritis, and thus possibly leading to a more sensitive characterization of osteoarthritic cartilage. Curvature of the cartilage surfaces combined with the low image resolution in relation to cartilage thickness set special requirements for an effective texture analysis tool. To introduce a novel implementation of GLCM algorithm optimized for cartilage texture analysis; to evaluate the performance of the designed algorithm against mean T relaxation time analysis; and to identify the most suitable texture features for discerning osteoarthritic subjects and asymptomatic controls. Case control. Eighty symptomatic osteoarthritis patients and 64 asymptomatic controls. Multislice multiecho spin echo sequence on a 3T MRI system. The T relaxation time maps were manually segmented by an operator trained for the task. Texture analysis was performed using an in-house algorithm developed in MATLAB. Symptomatic and asymptomatic subjects were compared using Mann-Whitney U-test. Repeatability of different features was addressed using the concordance correlation coefficient (CCC). Spearman's correlations between the features were determined. The algorithm displayed excellent performance in discerning symptomatic and asymptomatic subjects. Fifteen features provided a significant difference between the groups (P ≤ 0.05) and 12 of those had P values smaller than the mean T differences. Most of the studied texture features were highly repeatable with CCC over 90%. For the features with significant differences, correlation with mean T was low or moderate (|r| ≤ 0.5). With careful parameter and feature selection and algorithm optimization, texture analysis provides a powerful tool for assessing knee osteoarthritis with more sensitive detection of cartilage degeneration compared to the mean value of the T relaxation times in an identical region of interest. 2 Technical Efficacy Stage 2 J. Magn. Reson. Imaging 2018;47:1316-1327.